Quasi-thermal Photosphere Emission from Structured Jets of Gamma-Ray Bursts - Ding-Fang Hu; Jin-Jun Geng; Hao-Xuan Gao; Jing-Zhi Yan; Xue-Feng Wu (The Astrophysical Journal)
The prompt emission of gamma-ray bursts (GRBs) is supposed to be released from the relativistic jet launched from the central engine. Apart from the nonthermal nature of spectra in the majority of GRBs, there is evidence for the presence of quasi-thermal components in the prompt emission of a few GRBs according to observations by the Fermi satellite. On the other hand, the GRB jet has been revealed as structured in recent research. The theoretical spectra of photosphere emissions observed by an off-axis observer and the dependence of the spectra on the viewing angle under the assumption of structured jets remain unexplored. In this paper, we numerically calculate the instantaneous photosphere spectra by different viewing angles from a structured jet, from which relevant temporal and spectral characteristics are derived. Moreover, we address the necessity of proper treatment of the outflow boundary in the photosphere emission scenario. Furthermore, our calculations suggest that the Einstein Probe and Space-based Multi-band Astronomical Variable Object Monitor will have the capability to detect short GRBs similar to GRB 170817A up to a luminosity distance of 200 Mpc if the off-axis viewing angle is less than 10°.